A Reduction in ADAM17 Expression Is Involved in the Protective Effect of the PPAR-α Activator Fenofibrate on Pressure Overload-Induced Cardiac Hypertrophy. (19th July 2018) - Zeng, Si-Yu; Lu, Hui-Qin; Yan, Qiu-Jiang; Zou, Jian
Abstract : The peroxisome proliferator-activated receptor- α (PPAR- α ) agonist fenofibrate ameliorates cardiac hypertrophy; however, its mechanism of action has not been completely determined. Our previous study indicated that a disintegrin and metalloproteinase-17 (ADAM17) is required for angiotensin II-induced cardiac hypertrophy. This study aimed to determine whether ADAM17 is involved in the protective action of fenofibrate against cardiac hypertrophy. Abdominal artery constriction- (AAC-) induced hypertensive rats were used to observe the effects of fenofibrate on cardiac hypertrophy and ADAM17 expression. Primary cardiomyocytes were pretreated with fenofibrate (10 μ M) for 1 hour before being stimulated with angiotensin II (100 nM) for another 24 hours. Fenofibrate reduced the ratios of left ventricular weight to body weight (LVW/BW) and heart weight to body weight (HW/BW), left ventricular anterior wall thickness (LVAW), left ventricular posterior wall thickness (LVPW), and ADAM17 mRNA and protein levels in left ventricle in AAC-induced hypertensive rats. Similarly, in vitro experiments showed that fenofibrate significantly attenuated angiotensin II-induced cardiac hypertrophy and diminished ADAM17 mRNA and protein levels in primary cardiomyocytes stimulated with angiotensin II. In summary, a reduction in ADAM17 expression is associated with the protective action of PPAR- α agonists against pressure overload-induced cardiac hypertrophy.